Charlie and the great glass elevator - Dahl, Roald (Puffin, 2016)
Whoosh! Inside the Great Glass Elevator, Willy Wonka, Charlie Bucket and his family are cruising a thousand feet above the chocolate factory. They can see the whole world below them, but they're not alone. The American Space Hotel has just launched. Lurking inside are the Vernicious Knids - the brutal, vindictive murderous beasts in the universe.